2013
DOI: 10.1111/ijfs.12169
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on phenolic profile, vitamin C content and antioxidant activity of Italian honeys of different botanical origin

Abstract: Summary The aim of our study was to identify and quantify the phenolic acids, flavonoids and vitamin C and to evaluate the antioxidant activity in ninety Italian honeys of different botanical origins (chestnut, sulla, eucalyptus, citrus and multifloral). The results showed that total phenolic and flavonoid contents varied from 11.08 to 14.26 mg GAE per 100 g honey and from 5.82 to 12.52 mg QE per 100 g honey, respectively. HPLC–UV analysis showed a similar but quantitatively different phenolic profile of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
62
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 71 publications
16
62
3
Order By: Relevance
“…p-OH benzoic, cumaric acid, protocatechuic acid and caffeic acid were identified as the major phenolic compounds among the tested substances. Similarly to our own findings, one previous study reported that chestnut honeys with a major pollen content exceeding 70% were rich in caffeic acid, catechin and chlorogenic acid 38 . Phenolic acid standard chromatographic (Figure 1) and RP-HPLC-UV validation parameters of phenolic compounds (Table 6).…”
Section: Resultssupporting
confidence: 90%
“…p-OH benzoic, cumaric acid, protocatechuic acid and caffeic acid were identified as the major phenolic compounds among the tested substances. Similarly to our own findings, one previous study reported that chestnut honeys with a major pollen content exceeding 70% were rich in caffeic acid, catechin and chlorogenic acid 38 . Phenolic acid standard chromatographic (Figure 1) and RP-HPLC-UV validation parameters of phenolic compounds (Table 6).…”
Section: Resultssupporting
confidence: 90%
“…They concluded that chestnut honeys are the unifloral honeys with the highest antioxidant capacity when compared with other types of honey such as eucalyptus or blackberry honey. Finally the high phenol content was in concordance with other dark honeys from other geographical areas (Küçük et al, 2007;Kolayli et al, 2008;Sarikaya et al, 2009;Giorgi et al, 2011;Perna et al, 2013). The importance of the phenolic compounds on the honey matrix was considered by various researches because phenolic compounds are important components for human health (Bertoncelj et al, 2007;Küçük et al, 2007).…”
Section: Discussionsupporting
confidence: 76%
“…One of the methods widely used is the DPPH scavenging ability (Ahn et al, 2007). The high antioxidant potential for sweet chestnut honeys was cited by other authors, for honeys from Turkey (Küçük et al, 2007;Kolayli et al, 2008;Sarikaya et al, 2009), Italy (Pichichero, Canuti, & Canini, 2009;Giorgi et al, 2011;Perna et al, 2013), and Slovenia (Bertoncelj et al, 2007). Sarikaya et al, (2009) noted that chestnut propolis and chestnut honeys may protect humans from deleterious oxidative processes as a result of the antioxidative activity of the chestnut propolis and chestnut honeys.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations